Advances in Neuroergonomics and Cognitive Engineering Proceedings of the AHFE 2017 International Conference on Neuroergonomics and Cognitive Engineering, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Baldwin, Carryl; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book offers a broad perspective on the field of cognitive engineering and neuroergonomics, covering emerging practices and future trends toward the harmonious integration of human operators with computational systems. It reports on novel theoretical findings on mental workload and stress, activity theory, human reliability, error and risk, and neuroergonomic measures alike, together with a wealth of cutting-edge applications. Further, the book describes key advances in our understanding of cognitive processes, including mechanisms of perception, memory, reasoning, and motor response, with a special emphasis on their role in interactions between humans and other elements of computer-based systems. Based on the AHFE's main track on Neuroergonomics and Cognitive Engineering, held on July 17-21, 2017 in Los Angeles, California, USA, it provides readers with a comprehensive overview of the current challenges in cognitive computing and factors influencing human performance.
Keywords: Computational intelligence; User interfaces (Computer systems).; Human-computer interaction; Cognitive psychology; Neurosciences; Computational Intelligence; User Interfaces and Human Computer Interaction; Cognitive Psychology; Neuroscience